Images of Change : Visual Representations of Papal Power in Rome Following the Council of Trent. - Delgado-Jermann, Teresa. (Taylor & Francis Group, 2023)
Images of Change focuses on the visual propaganda employed by Catholic popes in Rome during the time of Tridentine Reform.